Peningkatan Produktivitas Petani Lahan Kering Melalui Optimalisasi Penerapan Sistem Usahatani Ekologis Terpadudi Lombok Utara - I Ketut Ngawit; Ni Made Laksmi Ernawati; Nihla Farida (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2018)
The main problem faced by farmers in development area of dryland in North Lombok is low soil productivity and farmer entrepreneurial ability and also system utilization of Crop and life stock animals relation is still poor. Actions taken to overcome those problems are training and action review by using demonstration plot (demplot) and direct assistance of activities implementing team toward farmers about application of integrated ecological farming design, assistance of weeds processing, forage, and agricultural waste became silase and hay. Based on evaluation result of all activities and economic analyses of applied farming model, several principal output were obtained i.e. target farmers followed enthusiastically training activities and implementation of demplot. The technology input model introduced gave high enough yield. More benefits are obtained with application of this integrated ecological farming design because easier plants maintenance, irrigation efficiency, and farmers can always supply vegetables commdities everyday so that marketting is easier. The success of participants in weeds processing and agricultural waste became silase and hay, besides being able to provide value added economically it is also very profitable agronomically because it can prevent plants from weeds and soil fertility for sustainable farming.